Building Organizational Capacity for Change - Judge, William Q (Business Expert Press, 2011)
Ebook from IG Library ; Never before have strategic leaders been confronted with so much overwhelming change. The traditional approach taken by the leader or leaders is to direct or control the organization's reaction on a monthly, weekly, or even daily basis. This approach is stressful and overwhelming for executive leaders, makes middle managers feel torn between honoring their senior leaders and listening to the demands of frontline employees, and is alienating for frontline employees. This approach is hardly a prescription for the pursuit of excellence, and does not enable the organization to be sufficiently agile or nimble to cope with the "white water" conditions in which the organization typically finds itself.